A formação permanente dos professores de um centro de educação infantil: o projeto especial de ação em pauta - Alves, Tatiana Nogueira (2025)
This dissertation focuses on the ongoing professional development of teachers at an Early Childhood Education Center. It aims to address the following questions: What are the teachers’ perceptions regarding the studies conducted within the Special Action Project (Projeto Especial de Ação – PEA)? How are the reflections from these formative moments integrated into daily pedagogical practices and aligned with the School Unit’s Political-Pedagogical Project (PPP)? Based on these inquiries, the general objective is to analyze how ongoing teacher training takes place in an Early Childhood Education Center. The specific objectives of the research are: (1) to identify teachers' perceptions regarding the studies conducted within the Special Action Project; (2) to verify how the reflections from these formative moments are articulated in daily pedagogical practices and in connection with the School Unit’s Political-Pedagogical Project. The premise is that discussions occurring during training sessions do not always align with the everyday and urgent practices surrounding the routines of babies and young children in the School Unit. These themes sometimes hinder dialogue and do not contribute to a reflective approach to pedagogical work. The research was conducted in an Early Childhood Education Center that serves babies and children from 0 to 3 years old, located in the city of São Paulo. The participants are three teachers. The methodology is qualitative, and the data collection procedures include observation and transcription of PEA meetings, semi-structured interviews with the teachers, as well as analysis of federal and municipal documents and the School Unit’s Political-Pedagogical Project. The interviews are analyzed using Bardin’s content analysis method, and after an initial overview (floating reading), three categories were identified: the methodology of PEA meetings, time allocated for documentation during PEA hours, and the relationship between PEA studies and pedagogical practice. The theoretical framework is based on the ideas of the following authors: Paulo Freire, Maurice Tardif, and Francisco Imbernón. The data indicate that the adopted methodology directly impacts the group’s engagement during the studies. The facilitator's approach to conducting meetings should consider the different ways people learn, selecting appropriate resources for the group and reflecting on their role as a connector of individual and collective formative work. Another issue addressed is the need to reassess the quality of time within these training spaces so that teachers can document their experiences, reframe their practices, and share their work with colleagues. Lastly, while the PEA sessions help deepen knowledge on specific topics, the teachers believe these sessions could improve in terms of organizing support materials, regularly evaluating meetings, and allowing more time to discuss urgent matters that arise in daily routines with the children. To support teachers and facilitators, a practice guide was created, aiming to present the general aspects of the Special Action Project, give visibility to collective formative processes, and assist newly hired teachers in the São Paulo Municipal Education Network.